Hypermethylation of DHRS3 as a Novel Tumor Suppressor Involved in Tumor Growth and Prognosis in Gastric Cancer - Sumei, Sha; Xiangyun, Kong; Fenrong, Chen; Xueguang, Sun; Sijun, Hu; Bin, Bai; Xiaolei, Shi; Yongjiu, Tu; Kaichun, Wu; Qingchuan, Zhao; Yongzhan, Nie; Bin, Xu (Frontiers in Cell and Developmental Biology, 2021)
Background/Aims: The role of DHRS3 in human cancer remains unclear. Our study explored the role of DHRS3 in gastric cancer (GC) and its clinicopathological significance and associated mechanisms. Materials: Bisulfite-assisted genomic sequencing PCR and a Mass-Array system were used to evaluate and quantify the methylation levels of the promoter. The expression levels and biological function of DHRS3 was examined by both in vitro and in vivo assays. A two-way hierarchical cluster analysis was used to classify the methylation profiles, and the correlation between the methylation status of the DHRS3 promoter and the clinicopathological characteristics of GC were then assessed. Results: The DHRS3 promoter was hypermethylated in GC samples, while the mRNA and protein levels of DHRS3 were significantly downregulated. Ectopic expression of DHRS3 in GC cells inhibited cell proliferation and migration in vitro, decreased tumor growth in vivo. DHRS3 methylation was correlated with histological type and poor differentiation of tumors. GC patients with high degrees of CpG 9.10 methylation had shorter survival times than those with lower methylation. Conclusions: DHRS3 was hypermethylated and downregulated in GC patients. Reduced expression of DHRS3 is implicated in gastric carcinogenesis, which suggests DHRS3 is a tumor suppressor.